2014
DOI: 10.1002/ange.201405485
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for a Peroxide Intermediate and a Reactive Enzyme–Substrate–Dioxygen Configuration in a Cofactor‐free Oxidase

Abstract: This work was supported by the UK Biotechnology and Biological Sciences Research Council (BBSRC) (grant number BB/I020411/1) to R.A.S. We acknowledge the use of the NIH Biowulf cluster and the EPSRC UK National Service for Computational Chemistry Software (NSCCS) in carrying out this work. We thank B. Castro and M. El Hajji (Sanofi-Aventis, Montpellier, France) for supplying purified UOX for some experiments. We are grateful to D. Heyes and N. S. Scrutton of the Manchester Institute of Biotechnology for the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…More recently, enzyme catalysis in copper nitrite reductase has been elucidated by serial synchrotron crystallography (SSX) at 100 K [75] (see below). Furthermore, the catalytic cycle of the non-chromophore-containing urate oxidase, kick-started by X-ray absorption, has been studied by combining in crystallo Raman spectroscopy, QM/MM simulations and X-ray crystallography [76].…”
Section: X-ray Induced Changes In Chromophore-containing Proteins At mentioning
confidence: 99%
“…More recently, enzyme catalysis in copper nitrite reductase has been elucidated by serial synchrotron crystallography (SSX) at 100 K [75] (see below). Furthermore, the catalytic cycle of the non-chromophore-containing urate oxidase, kick-started by X-ray absorption, has been studied by combining in crystallo Raman spectroscopy, QM/MM simulations and X-ray crystallography [76].…”
Section: X-ray Induced Changes In Chromophore-containing Proteins At mentioning
confidence: 99%
“…Describing both the quantum chemistry required for accurate description of reactions as well as the complex structural/dynamical aspects of the protein/nucleic acid environment, hybrid quantum/classical QM/MM methods have a unique, unprecedented capability to examine reaction mechanisms at sub-atomic details. An extensive amount of work has been done toward understanding various enzymatic systems such as lipoxygenases [1,2], cofactor-free oxidases [3,4], Kemp eliminase [5,6], serine hydroxymethyltransferase [7] and many others [8][9][10][11][12][13]. Here we focus on phosphate catalytic reactions, which contribute probably the most important catalytic reactions in living organisms [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive computational details of the reaction mechanisms of coproporphyrinogen oxidase (Silva & Ramos, 2008) and vitamin K.-dependent glutamate carboxylase (Silva & Ramos, 2007) confirmed that substrate deprotonation is indeed required for their catalytic action. Evidence for substrate deprotonation is also available for urate oxidase (Bui et al, 2014), although in this instance a more complex mechanism involving transient protein-based free radicals was proposed to be operative, based on EPR measurements of anaerobic preparations of substrate-bound enzyme (Gabison et al, 2011). Based on the reaction profile towards a superoxide-scavenging spin probe, radical-pair reactivity towards O 2 has also been suggested to occur (Thierbach et al, 2014) in a bacterial ring-cleaving 2,4-PeerJ reviewing PDF | (2016:01:8687:3:0:NEW 10 Nov 2016)…”
Section: Introductionmentioning
confidence: 99%